#### Answer

$-3t\sqrt {11r}$

#### Work Step by Step

$5t\sqrt {11r}-8t\sqrt {11r}=\sqrt {11r}\times(5t-8t)=\sqrt {11r}\times(-3t)=-3t\sqrt {11r}$

Published by
Brooks Cole

ISBN 10:
0-53449-636-9

ISBN 13:
978-0-53449-636-4

$-3t\sqrt {11r}$

$5t\sqrt {11r}-8t\sqrt {11r}=\sqrt {11r}\times(5t-8t)=\sqrt {11r}\times(-3t)=-3t\sqrt {11r}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.